If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 4) = 2(-8 + -1x) + -2 Reorder the terms: 2(4 + x) = 2(-8 + -1x) + -2 (4 * 2 + x * 2) = 2(-8 + -1x) + -2 (8 + 2x) = 2(-8 + -1x) + -2 8 + 2x = (-8 * 2 + -1x * 2) + -2 8 + 2x = (-16 + -2x) + -2 Reorder the terms: 8 + 2x = -16 + -2 + -2x Combine like terms: -16 + -2 = -18 8 + 2x = -18 + -2x Solving 8 + 2x = -18 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 8 + 2x + 2x = -18 + -2x + 2x Combine like terms: 2x + 2x = 4x 8 + 4x = -18 + -2x + 2x Combine like terms: -2x + 2x = 0 8 + 4x = -18 + 0 8 + 4x = -18 Add '-8' to each side of the equation. 8 + -8 + 4x = -18 + -8 Combine like terms: 8 + -8 = 0 0 + 4x = -18 + -8 4x = -18 + -8 Combine like terms: -18 + -8 = -26 4x = -26 Divide each side by '4'. x = -6.5 Simplifying x = -6.5
| 1+2p-8p=-5(p-5)+4(5p-6) | | X+1.6=9.8 | | x-53=47-x | | m=2.333333333n+0.3333333333p | | 5(2r-3)=10r-15 | | 8+4(3+7x)=4(10x+5) | | 4x+16x-10y=180 | | 18y-6y=11(y+2)+y | | 2x^2+2x-12=-12 | | -12=2x^2+2x-12 | | 2x-x+x-x+6x=21 | | 21-4s=0.5s | | 5x+21(x-3)=197 | | 6x-4(x-4)=-2x+40 | | 5(2t+1)-8=4t-3(1-2t) | | 6x^2-xy-2y^2= | | 0.92x+0.98(12-x)=0.096(12) | | (x^2)-5x-3=0 | | 6.1(3.1+2.5x)=15.3x-3.9-1 | | 4x-28=5-2x | | -7x-28=-5(8+x) | | X+2x-4=3x+7 | | 2x+4y=-8fory | | 3b^2+16b+15= | | x-3=3(47-x) | | 3+x+2x=-12 | | 6-8p=35 | | c^2+4bc+3b^2= | | 50-x-3=47-x | | -3w^2+7w-66=0 | | -4x-44=-7x+16 | | 147=7m+7 |